A study of cadaver decomposition in sandy soil of East Coast of Peninsular Malaysia / Siti Sofo Ismail - Ismail, Siti Sofo; Saminadan, Shamini A/P; Daud, Nur Anisah (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
A simulated burial experiment was carried out to evaluate the potential of soil lipids, as indicator for estimating the post mortem interval. The findings of this study will provide baseline data for decomposition of cadaver in sandy soil. The fatty flesh of pig carcass (Sus scrofa) was buried in sea soils, mimicking the burial in a shallow grave. The modification of Bligh-dyer extraction was used for the lipids extraction process. The soil pH was measured to identify the effect of decomposing body on the soil acidity. The soil pH was acidic in early stage and gradually increased corresponding to the next stage of decomposition. The gas chromatography with flame ion detector was employed to determine the concentration of cadaveric material that may be introduced at each stage of the decomposition process. The results showed the abundance of free fatty acids, palmitic (C16:0) and stearic acids (C18:0). The concentrations of these acids vary upon decomposition stages. Conclusively, the composition of lipids for each stage of decomposition can be developed as potential biomarkers in order to estimate the post-mortem interval.